Mid-treatment adaptive planning during thoracic radiation using 68 Ventilation-Perfusion Positron emission tomography. (May 2023) - Bucknell, Nicholas; Hardcastle, Nicholas; Gunewardena, Roshini; Nguyen, Long; Callahan, Jason; Ball, David; Selbie, Lisa; Kron, Tomas; Turgeon, Guy-Anne; Hofman, Michael S.; Siva, Shankar
Highlights: Lung cancers are currently treated assuming all lung function is uniform. Lung function can be imaged using 68 Ventilation-Perfusion Positron Emission Tomography. Serial functional lung PET scans have demonstrated changes in lung function treatment course. These changes are different for the physiological processes of Ventilation and Perfusion. These changes should be considered when planning future functional lung avoidance trials. Abstract: Four-Dimensional Gallium 68 Ventilation-Perfusion Positron Emission Tomography ( 68 Ga-4D-V/Q PET/CT) allows for dynamic imaging of lung function. To date there has been no assessment of the feasibility of adapting radiation therapy plans to changes in lung function imaged at mid-treatment function using 68 Ga-4D-V/Q PET/CT. This study assessed the potential reductions of dose to the functional lung when radiation therapy plans were adapted to avoid functional lung at the mid-treatment timepoint using volumetric arc radiotherapy (VMAT). Methods: A prospective clinical trial (U1111-1138–4421) was performed in patients undergoing conventionally fractionated radiation therapy for non-small cell lung cancer (NSCLC). A 68 Ga-4D-V/Q PET/CT was acquired at baseline and in the 4th week of treatment. Functional lung target volumes using the ventilated and perfused lung were created. Baseline functional volumes were compared to the week 4 V/Q functional volumes to describe the change in function over time. For each patient, 3 VMAT plans were created and optimised to spare ventilated, perfused or anatomical lung. All key dosimetry metrics were then compared including dose to target volumes, dose to organs at risk and dose to the anatomical and functional sub-units of lung. Results: 25 patients had both baseline and 4 week mid treatment 68 Ga-4D-V/Q PET/CT imaging. This resulted in a total of 75 adapted VMAT plans. The HPLung volume decreased in 16/25 patients with a mean of the change in volume (cc) −28 ± 515 cc [±SD, range −996 cc to 1496 cc]. The HVLung volume increased in 13/25 patients with mean of the change in volume (cc) + 112 ± 590 cc. [±SD, range −1424 cc to 950 cc]. The functional lung sparing technique was found to be feasible with no significant differences in dose to anatomically defined organs at risk. Most patients did derive a benefit with a reduction in functional volume receiving 20 Gy (fV20) and/or functional mean lung dose (fMLD) in either perfusion and/or ventilation. Patients with the most reduction in fV20 and fMLD were those with stage III NSCLC. Conclusion: Functional lung volumes change during treatment. Some patients benefit from using 68 Ga-4D-V/Q PET/CT in the 4th week of radiation therapy to adapt radiation plans. In these patients, the role of mid-treatment adaptation requires further prospective investigation.